Aerospace technology in Peru - Roman Gonzalez, Avid (2015)
In recent years, Peru is trying to venture into the space age. Different universities as The Pontificia Universidad Catolica del Peru (PUCP), Universidad Alas Peruanas (UAP), and the Universidad Nacional de Ingenieria (UNI); they designed the first Peruvian nanosatelites. These nanosatelites were CubeSats; it is a cubic shape and measures 10× 10 × 10 cm with a mass of 1 kg approximately. In other hand, Peru signed a contract for the purchase of a remote sensing satellite that will be launched into orbit in July 2016. Also, there are Peruvian professionals and students participating in different missions for simulating Mars exploration.